Paleoceanographic Conditions of Neo-Tethys Deposits in Northeast Iraq (Shiranish Formation) by Geochemical Proxies - Al-Obaidi, Mutadhid; Abbas, Ibrahim Mustafa; Ahmed, Muaiad Tahir; Hussain, Salah Ali (Iraqi Journal of Science, 2022)
Geochemical proxies provide detailed information on depositional environment and diagenetic processes. The main objectives of the present study are the evaluation of the paleoenvironment and diagenetic conditions of selected three sections of the Shiranish Formation (Late Campanian-Maastrichtian) in Dokan-Sulaymaniyah, Kurdistan Region, northeast of Iraq. The major and some trace elements were analysed by X-Ray Fluoresces. These geochemical results showed a positive correlation of SiO2, Al2O3, Fe2O3, MgO and TiO2 between each other due to the influence of detrital influx from the active oceanic margins and thrust belts of the northeast Arabian Plate. The terrigenous supply of silicates (K-feldspar) and clay minerals (Illite) caused a positive correlation between K2O values and Al2O3. In general, there is a low abundance of SiO2 and Al2O3 contents, referring to the deepening of the Neo-Tythus ocean basin in the formation’s lower part. The Mn* factor of the lower and middle part of the formation exhibited anoxic conditions while oxic- suboxic conditions at the upper part. The Mn/Sr ratios were less than one, which means that Shiranish marly limestone was well preserved out of diagenetic processes. The paleoredox proxies Th/U, V/Cr &V/(V+Ni) confirmed that the lower part of the Formation was deposited in a relatively anoxic deep-outer shelf environment with a rising in paleoproductivity. In contrast, the upper part was characterised by dyoxic-oxic redox. Due to the inner shelf environment, this redox fluctuation reflects a regression phase of sea level, which is compatible with the closure events of the Neo-Tethys in the Eocene epoch.